1999
DOI: 10.1177/002246699903300303
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Changes in Teachers' Conduct of Student Pair Activities

Abstract: The purpose of this study was to examine the effectiveness of reciprocal peer coaching for promoting changes in teachers' conduct of student pair activities. A multiple baseline design was used to examine four conditions. Two kindergarten teachers implemented student-assisted learning activities alone during an initial baseline and then collaborated with another teacher during two coaching phases. Finally, each teacher participated in a final maintenance condition in which they conducted their activities in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 27 publications
4
42
0
1
Order By: Relevance
“…This finding is consistent with related peer-coaching literature focused on general education best practices (Gersten, Morvant, & Brengelman, 1995;Hasbrouck, 1997;Hudson, Miller, Salzberg, & Morgan, 1994;Kohler, Ezell, & Paluselli, 1999;Pugach & Johnson, 1995). Note.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is consistent with related peer-coaching literature focused on general education best practices (Gersten, Morvant, & Brengelman, 1995;Hasbrouck, 1997;Hudson, Miller, Salzberg, & Morgan, 1994;Kohler, Ezell, & Paluselli, 1999;Pugach & Johnson, 1995). Note.…”
Section: Discussionsupporting
confidence: 91%
“…Coaching has been effective in increasing teacher accuracy in a range of areas including implementation of classwide positive behavior supports (PBS; Filcheck, McNeil, Greco, & Bernard, 2004), reading interventions (Jager, Reezigt, & Creemers, 2002;Kohler, Ezell, & Paluselli, 1999;Lignugaris-Kraft & Marchand-Martella, 1993;Morgan et al, 1994), explicit math instruction , and teacher praise in an RTI model (Myers, Simonsen, & Sugai, 2011).…”
Section: Coachingmentioning
confidence: 99%
“…Third, the body of literature on coaching has shown that coaching can be effective in improving teachers' behavior when implementing classwide positive behavior supports (Filcheck et al, 2004), reading interventions (Jager et al, 2002;Kohler et al, 1999;Lignugaris-Kraft & Marchand-Martella, 1993;Morgan et al, 1994), explicit math instruction , and teacher praise in an RTI model (Myers, Simonsen, & Sugai, 2011). This study expands the areas where coaching has been shown to be effective to include teacher implementation of function-based interventions.…”
Section: Specific Contributions Of This Studymentioning
confidence: 99%
“…In the face of category-like and homogenising views, the most recent education trends contemplate teachers all-inclusive education view that centres more on specific institutional contexts and cultures that come, therefore, closer to schoolcentred training, action research, institutional analysis or organisational development. Once again, these approaches bring us nearer to the practice-reflexive professional whom we mentioned earlier, and to the school being a place where problems are solved and where work strategies are based on professional cooperation and collaboration (Alonso and Rodríguez 2004;Duran and Miquel 2004;Parrilla 2004), on classroom management regarding conflicts (Hasbrouck 1997;Morgan et al 1994;Pugach and Johnson 1995), and on training among teachers that may encourage positive attitudes towards inclusion (Downing, Morrison, and Berecin-Rascon 1996), facilitate interactions in classrooms, and may adapt teaching materials spontaneously, and the social roles and processes among students (Kohler, Ezell, and Paluselli 1999). All this has to be framed in research action processes, which allow one to reflect on a personal teaching model, a model that defines one s specific practice that is shaped by the influence of one s academic past as a student, by one s professional past as a teacher and by one s adaptation to the institutional and social context (Ainscow et al 2004).…”
Section: Discussion Of the Resultsmentioning
confidence: 99%